Fraud Detection: Application of COSO on Auditing Accounting Information Systems in Plantation Companies: Pendeteksian Fraud: Penerapan COSO pada Audit Sistem Informasi Akuntansi Pada Perusahaan Perkebunan - Anggraini, Leriza Desitama; Faradillah (Universitas Muhammadiyah Sidoarjo, 2022)
The research was conducted with the aim of developing internal controls in the accounting cycle, especially in accounting information systems based on the COSO Integrated Framework 2013. Internal control is very important for every company because it relates to the number of assets managed by the company. This research was conducted with a descriptive approach and method. The design of this research is a case study. Data collection techniques were carried out by interview and document inspection methods. After that, data collection is carried out as a source of information for internal control and obtaining. The results of this study indicate that the internal control of the accounting information system at PT XYZ is less effective so that the potential for vulnerability is still large. The accounting information system used today is still limited to data entry. Not yet have an integrated system that can support the company's business processes. This can open up opportunities for fraud to occur. In order to prevent or minimize the risk of the need for adequate control in the work unit, especially the accounting reporting unit through the accounting information system